Peningkatan Daya Saing UMKM Berbasis Inovasi Dan Kreativitas Di BSD Kota Tangerang Selatan - Attania Dwi Arniessa; Lia Nirawati (Politeknik Negeri Fakfak, 2024)
The intense competition in the business world creates a need for MSMEs to improve their business in order to compete in the market. For example, globalization has made it easy for goods and services to enter the country, resulting in high competition between domestic and foreign businesses. Therefore, in this era, the role of innovation becomes a determining factor in being able to compete in the market. This activity aims to increase the competitiveness of MSMEs in BSD, South Tangerang City based on innovation and creativity in response to the increasingly intense competition in the F&B world. This activity uses a survey method. Based on the survey results, the existing business actors in BSD, South Tangerang City do not have a good business model, do not have innovative menus that are different from other brands, and still do not have a digital marketing strategy. Therefore, a BMC business model, SWOT analysis, AIDA analysis, promotion strategy design, and new menu design were created for business actors to apply. To achieve this, this service activity uses a method consisting of three stages: analysis, presentation, and action. The results of this activity were able to bring about changes to MSME products in BSD, South Tangerang City in the form of opening new branches.